The Influence of Using Instagram @Infobnn_ri on Fulfilling BNN's Information Needs among Followers - Wahyuni, Sri; Kuncoroyakti, Yohanes Arie; Ohorella, Noviawan Rasyid; Putu, Ni Luh (Universitas Pendidikan Nasional, 2024)
Instagram social media is a platform that is widely used by the public and government agencies to interact, obtain information and share information widely and quickly using internet network technology. This is used by government agencies, the National Narcotics Agency of the Republic of Indonesia, in conveying ideas, ideas, programs and strategies to the public in order to realize state goals and fulfill the information needs of the public in obtaining information related to the National Narcotics Agency of the Republic of Indonesia via the Instagram account @infobnn_ri. The research on this account aims to find out whether there is an